Teknik Pengembangan Bahasa Anak Usia Dini melalui Bermain dan Berinteraksi (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to describe the techniques used to develop early childhood language skills through play and social interaction activities at TK Alkafani, Aek Galoga. Language ability is a crucial aspect of early childhood development, serving as the foundation for communication and future learning. This research employed a descriptive qualitative approach, utilizing observation, interviews, and documentation as data collection techniques. The findings reveal that role-playing, symbolic play, singing, and shared reading are effective techniques in stimulating children's language skills. Interactions between children and teachers, as well as among peers, contribute positively to the improvement of vocabulary, sentence structure, and speaking abilities. Through enjoyable and interactive approaches, children become more active in expressing ideas and thoughts verbally. This study recommends the implementation of play and interaction-based techniques as appropriate language learning strategies tailored to the developmental characteristics of early childhood.